Postglacial Isobases from Northern Ellesmere Island and Greenland: New Data - England, John; Bednarski, Jan (Géographie physique et Quaternaire)

(untitled) (Les Presses de l'Université de Montréal, 1986)
ABSTRACTOver seventy new 14C dates on former relative sea levels from Hall Land, northwest Greenland, and Clements Markham Inlet, northern Ellesmere Island, are combined with previous data to revise the regional isobases for this area. These isobases show : 1) a centre of maximum postglacial emergence over northwest Greenland extending to; 2) an intervening cell of lower emergence over northeast Ellesmere Island which was isostatically-dominated by the Greenland Ice Sheet; in turn, extending to 3) a higher centre of emergence over the Grant Land Mountains, northernmost Ellesmere Island, associated with the independent history of local ice caps there. Radiocarbon dates from raised marine shorelines show a 2000 year lag between glacial unloading on northwest Greenland and northernmost Ellesmere Island. This lag in glacioisostatic adjustments suggests a considerable range in the glacier response times and/or glacioclimatic regimes in this area. Throughout the area the last ice limit was ca. 5-60 km beyond present ice margins. Maximum emergence at these ice limits is marked by shorelines built into a full glacial sea which range from 124 m asl in Clements Markham Inlet to 150 m asl in Hall Land. This indicates that similar emergence (120-150 m) in other areas does not necessarily require the removal of entire ice sheets although this has been commonly assumed in the literature. The geophysical implications of this warrant consideration.